Implementing Total Quality Management in Public Infrastructure Projects: A Case Study of the Trasan II Bridge Construction - Wibisono, Ilham Dhimas; Isfianadewi, Dessy; Sudrajat, Yusuf Ahmad (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2025)
This study investigates the implementation of Total Quality Management (TQM) principles in a mid-scale infrastructure project: the construction of the Trasan II Bridge in Klaten Regency, Indonesia. The research addresses the question of how TQM can be operationalized to improve quality assurance and time efficiency in public sector construction. Using a single case study approach, data were collected through document analysis (including MC-0, MC-P1, and technical reports), direct observation, and simulated semi-structured interviews with four key informants. The findings reveal that early-stage planning through Mutual Check 0 (MC-0) fosters clarity and coordination among stakeholders, while Mutual Check P1 (MC-P1) and material validation particularly tensile testing of reinforcing steel enhance quality control and reduce risk. Furthermore, structured scheduling, continuous monitoring, and reporting mechanisms contributed to schedule adherence and operational discipline. The integration of qualitative and quantitative evidence through triangulation reinforces the validity of the results. The study concludes that TQM, when embedded systematically from planning to execution, can serve as a practical framework for improving performance outcomes in public infrastructure projects, especially in developing country contexts.